2017
DOI: 10.1371/journal.pone.0183832
|View full text |Cite
|
Sign up to set email alerts
|

Lower frequency of TLR9 variant associated with protection from breast cancer among African Americans

Abstract: IntroductionToll-like receptor 9 (TLR9) is an innate immune system DNA-receptor that regulates tumor invasion and immunity in vitro. Low tumor TLR9 expression has been associated with poor survival in Caucasian patients with triple negative breast cancer (TNBC). African American (AA) patients with TNBC have worse prognosis than Caucasians but whether this is due to differences in tumor biology remains controversial. We studied the prognostic significance of tumor Toll like receptor-9 (TLR9) protein expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The lower improvement in the Caucasian population with the same disease category may indicate that in fact, a limit of effectiveness of treatment for hormone receptor negative disease has been reached with current therapies and that African American patients are catching up to these limits. It is entirely possible that the bridging of disparities in survival in this subpopulation may reach a limit with current therapy due to reported biological differences responsible for more aggressive behavior of hormone negative cancer in African American women (55)(56)(57)(58)(59). Nevertheless, our study is the first to demonstrate that African Americans with ER-and PR-disease benefitted significantly more than Caucasians with ER-and PR-disease in the 21 st century.…”
Section: Discussionmentioning
confidence: 64%
“…The lower improvement in the Caucasian population with the same disease category may indicate that in fact, a limit of effectiveness of treatment for hormone receptor negative disease has been reached with current therapies and that African American patients are catching up to these limits. It is entirely possible that the bridging of disparities in survival in this subpopulation may reach a limit with current therapy due to reported biological differences responsible for more aggressive behavior of hormone negative cancer in African American women (55)(56)(57)(58)(59). Nevertheless, our study is the first to demonstrate that African Americans with ER-and PR-disease benefitted significantly more than Caucasians with ER-and PR-disease in the 21 st century.…”
Section: Discussionmentioning
confidence: 64%
“…Perhaps our most exciting finding is the observed racial differences in mtDNA, especially with aggressive clinical phenotypes. Genome-wide association studies have identified susceptible genetic variants for sarcoidosis among African Americans [44], and racial differences in innate immunity have been demonstrated, particularly in TLR9 polymorphisms related to breast cancer [45] and infectious granulomas [46], and in TLR9 expression in systemic lupus erythematosus [47]. An association between TLR9 and sarcoidosis has been reported [48], although racial differences have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison study of African American (AA) and European American (EA) breast cancer patients, the association of rs352140 was investigated. It was found that rs352140 SNP, located at the CpG site, has a protective effect that is 1.6X more common in EA compared to AA [71]. In contrast, Etokebe et al found no association of rs352140 with breast cancer among 130 case samples of Croatian patients [72].…”
Section: • Association Between Tlr9 Polymorphisms and Cancer Riskmentioning
confidence: 97%